(untitled) (translation. a transdisciplinary journal, 2021)
The writings of Frantz Fanon were very quickly subjected to a form of cultural translation, not only in some of the more esoteric interpretations of his work, which take it very far from his own historical concerns, but also more literally : for today, for the most part, he is read in translation. Sales of his books in English far outnumber those of his original texts in French.